Robotics: Science and Systems XIII 2017
DOI: 10.15607/rss.2017.xiii.024
|View full text |Cite
|
Sign up to set email alerts
|

Groups of humans and robots: Understanding membership preferences and team formation

Abstract: Abstract-Although groups of robots are expected to interact with groups of humans in the near future, research related to teams of humans and robots still appears scarce. This paper contributes to the study of human-robot teams by investigating how humans choose robots to partner with in a multi-party game context. The novelty of our work concerns the successful design and development of two social robots that are able to autonomously interact with a group of two humans in the execution of a social and enterta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Robots and humans have inevitably come together as teams to complete tasks and share resources (Correia et al, 2019). The appearance and behavior of robots can be very similar to humans, and we treat robots as if they possess human attributes, including morality (Coeckelbergh, 2014).…”
Section: Purpose and Hypothesesmentioning
confidence: 99%
“…Robots and humans have inevitably come together as teams to complete tasks and share resources (Correia et al, 2019). The appearance and behavior of robots can be very similar to humans, and we treat robots as if they possess human attributes, including morality (Coeckelbergh, 2014).…”
Section: Purpose and Hypothesesmentioning
confidence: 99%
“…Lastly, we performed a behavioral analysis on the data collected in the aforementioned (Raque et al, 2018;Oliveira, Arriaga, Correia, & Paiva, 2020), using a coding scheme based on Bales Interaction Process Analysis (Bales, 1950). We found that the structure of the group's communication is different according to the goal orientation of the robot and according to 538 F. Correia, F. S. Melo, A. Paiva / Topics in Cognitive Science 16 (2024) Table 2 Analysis of the first use case (Correia et al, 2017a;Correia et al, 2017bCorreia et al, , 2018b -Choice of robot for hypothetical future game their roles. Overall, the occurrence of different behavioral patterns in competitive and collaborative interactions with robots suggests that there might be a relationship between social cohesion and structural cohesion in human-robot interactions.…”
Section: A Use Case On Social Cohesionmentioning
confidence: 99%
“…For instance, some researchers explored how robots can help mitigate conflicts in teams and how a robot's gaze influences its teammates' perception of decision making [65,110]. Additionally, Correia et al [29] explored how human group members in a two-human, two-robot group generate their membership preferences to these robots based on the robot's behaviors.…”
Section: Groups In Hrimentioning
confidence: 99%
“…In these environments, robots are often tasked with interacting with groups of people. Thus, it is 15:2 A. Taylor et al important that robots have an adequate understanding of social groups [22,30,44,59,61,62,66,77,79,83,84,90,96,129,132,133].…”
Section: Introductionmentioning
confidence: 99%